THE SOCIAL IMPACT OF THE MYTH OF DEMOTION AT BAJANG RATU TEMPLE FOR THE PEOPLE OF DUSUN PELEM: DAMPAK SOSIAL MITOS PENURUNAN JABATAN DI CANDI BAJANG RATU BAGI MASYARAKAT DUSUN PELEM - Aulia Zahra Fadhila; Eggy Fajar Andalas; Joko Widodo (Jurnal Kata, 2023)
This study aims to find the social consequences of the demotion myth associated with the Bajang Ratu temple among the residents of Pelem Hamlet. Employing a qualitative methodology with an ethnographic approach, the research utilized interviews, observations, and documentation techniques. The data analysis involved processes such as data reduction, data presentation, and drawing conclusions. The findings of the study reveal that the demotion myth has become a long-standing tradition passed down through generations for several decades. The social impacts stemming from the demotion myth at the Bajang Ratu Temple include: (1) reluctance among many officials to enter the Bajang Ratu Temple, (2) the practice of circumambulating the temple once as part of the tradition, (3) the necessity of using polite language, and (4) a significant proportion of Bajang Ratu Temple visitors being officials.